Produção de nanofibras de policaprolactona e poli(álcool vinílico) /colágeno tipo I por eletrofiação coaxial para regeneração de pele - Anaya Mancipe, Javier Mauricio (2018)
The main goal of this work was to develop nano-structured films composed of coaxial fibers of collagen type I / polyvinyl alcohol (shell) and polycaprolactone (PCL) in the core, using the electrospinning technique, aiming its application for skin regeneration. Initially, the influence of solvent system, flow, voltage and distance traveled on the morphology of PCL and Col_1 / PVA mixture monolithic fibers electrospun separately were analyzed. The best conditions for the formation of coaxial nanofibers, having PCL in the core and Col_1 / PVA in the shell were evaluated. Nanofibers core - shell with mean diameter of 346 nm were obtained with Col_1 / PVA:PCL flow ratio of 1:4, distance needle to collector of 12 cm and voltage of 16 kV. Following these conditions, the characteristic triple helical structure of the collagen molecule was maintained. The nanostructured film showed swelling capacity, collagen release, morphology and non-cytotoxicity suitable for application in tissue regeneration, being a potential dressing for skin lesion.